Consumption of carbonated soft drinks among Ghanaian adolescents: associations with socio-demographic factors, health risk factors and psychological distress. Issue 3 (October 2021) - Atorkey, Prince; Akwei, Mariam; Asare-Doku, Winifred
Background: Carbonated soft drinks consumption is associated with weight gain and other chronic diseases. Aim: To examine whether socio-demographic factors, health risk factors and psychological distress are associated with carbonated soft drink consumption among adolescents in selected senior high schools in Ghana. Methods: Data were obtained from the 2012 Ghana Global School-based Student Health Survey (GSHS). Participants consisted of 1756 school-going adolescents sampled using a two-stage cluster sampling method. Binomial logistic regression was used to determine whether socio-demographic factors, health risk factors and psychological distress were associated with consumption of soft drinks. Results: The prevalence of carbonated soft drinks consumption was 34.9%. Males (odds ratio (OR) = 0.73 (95% confidence intervals (CI) 0.59–0.92); p = 0.007), and participants with high socio-economic status (OR = 0.76 (95% CI 0.48–0.97); p = 0.033) had smaller odds for consumption of soft drinks. Also, adolescents in Senior High School (SHS) 3 (OR = 0.72 (95% CI 0.53–0.97); p = 0.034) and SHS 4 (OR = 0.63 (95% CI 0.43–0.91); p = 0.014) had smaller odds for soft drinks intake compared to those in SHS 1. Health risk factors associated with greater odds of high soft drink consumption were tobacco use (OR = 1.68, (95% CI 1.07–2.65); p = 0.025), fast food consumption (OR = 1.88, (95% CI 1.47–2.41); p = 0.011) and alcohol consumption (OR = 1.43, (95% CI 1.02–1.99); p = 0.039). Consuming adequate fruit (OR = 0.19 (95% CI 0.15–0.24); p = 0.000) and adequate vegetable (OR = 0.55 (95% CI 0.34–0.87); p = 0.011) were associated with lower odds for soft drink consumption. Adolescents who reported feeling anxious had smaller odds for soft drink intake (OR = 0.65, (95% CI 0.47–0.91); p = 0.011). Conclusions: The findings from this study show that socio-demographic characteristics, health risk factors and psychological distress are associated with the soft drink consumption among adolescents in Ghana. Interventions aimed at reducing soft drink consumption and other health risk factors are needed.